Estratégias restauradoras simplificadas para dentes decíduos: redução do tempo de condicionamento da dentina e uso de resina de incremento único (bulk-fill) - Gindri, Larissa D'Olanda (2023)
This thesis is composed of two scientific articles, which evaluated two simplified adhesive strategies used in primary teeth. The first study investigated, by a systematic review and metaanalysis, the influence of reduced dentin etching (acid-etching or acidic primer) time on the bond strength of adhesive systems to primary teeth. The search was performed in PubMed, Web of Science, and Scopus databases. Eight studies were included in the systematic review and seven in the meta-analysis. The shortening etching time did not influence the immediate dentin bond strength for etch-and-rinse (Z=0.07, p=0.95) or self-etch systems (Z=0.41, p=0.69). After aging, however, the shorting etching time improved the bond strength for etch-and-rinse adhesives (Z=2.01, p=0.04). All studies presented a high bias risk. In conclusion, the reduction of dentin etching time does not jeopardize the adhesion in primary teeth for etch-and-rinse or self-etch adhesives, and the reduction of acid-etching time contributed to resin-dentin bonding stability over time. The second study is a randomized clinical trial, which aimed to compare the clinical performance and the time required to restore occlusal-proximal lesions in primary molars, using a bulk-fill resin (FiltekTM Bulk-fill, 3M ESPE) and a conventional resin (Filtek Z350 XT, 3M ESPE). 140 occlusal-proximal restorations in primary molars of 65 participants performed in random order, 70 with each of the two resins were evaluated by a single calibrated examiner, using the criteria of the World Dental Federation (FDI), in the immediate (baseline), after 6 and 12 months. The clinical time was measured using a digital timer, considering the time from insertion to the final photoactivation of the resin. The success and survival of the restorations were evaluated using Kaplan-Meier estimates and compared using the log-rank test. The difference in clinical restorative time was compared using the Mann-Whitney U test. The significance level was 5%. After 12 months, 115 restorations were evaluated and the probability of success was 88.7% for restorations performed with conventional resin and 85.9% for bulk-fill resin. Survival estimates were 90% and 93.7%, respectively, for restorations with conventional and bulk-fill resins. No significant differences were found between the success (p=0.62) and survival (p=0.51) curves. The main cause of failure of restorations was related to problems in marginal adaptation. The bulk-fill resin required 30% less time than the conventional resin (p<0.001). Bulk-fill resin presents similar clinical performance to that of conventional resin, with reduced clinical restorative time, thus being an option for restoring occlusal-proximal lesions in primary molars.